2022
DOI: 10.3390/ma15155142
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Tensile Properties of Different Infill Pattern Structures of 3D-Printed PLA Polymers: Analysis and Validation Using Finite Element Analysis in ANSYS

Abstract: The advancement of 3D-printing technology has ushered in a new era in the production of machine components, building materials, prototypes, and so on. In 3D-printing techniques, the infill reduces the amount of material used, thereby reducing the printing time and sustaining the aesthetics of the products. Infill patterns play a significant role in the property of the material. In this research, the mechanical properties of specimens are investigated for gyroid, rhombile, circular, truncated octahedron, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Hence, there are possibilities of an increase in tensile strength due to increased material infill density. Although the printing speed did not directly affect the infill densities, the printing time increased with infill density . However, the investigation by Miazio suggested that the strength of the samples decreased with increasing speed .…”
Section: Parameters Affecting the Printing Performancementioning
confidence: 84%
See 1 more Smart Citation
“…Hence, there are possibilities of an increase in tensile strength due to increased material infill density. Although the printing speed did not directly affect the infill densities, the printing time increased with infill density . However, the investigation by Miazio suggested that the strength of the samples decreased with increasing speed .…”
Section: Parameters Affecting the Printing Performancementioning
confidence: 84%
“…Although the printing speed did not directly affect the infill densities, the printing time increased with infill density. 57 However, the investigation by Miazio suggested that the strength of the samples decreased with increasing speed. 58 This might be because, at a higher print speed, vibrations of the nozzle may induce instability that can be observed as visual waves on the printed item.…”
Section: Parameters Affecting the Printing Performancementioning
confidence: 99%
“…The single, bilayer, and multilayer coating of tool inserts leads to increasing wear resistance properties and metal removal ability. The recent advancements of nanolayered coatings lead to a reduction of ball sizes which increases the adhesive property [61,62]. The increasing adhesive property reduces the adhesive wear of tool inserts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many types of 3D printing technology for constructing plastic materials, such as stereolithography (SLA), selective laser sintering (SLS), fused deposition molding (FDM), selective laser melting (SLM), laminated object manufacturing (LOM), digital beam melting (EBM), and digital light processing (DLP) have been rapidly developed [ 5 ]. Among them, FDM and SLA are the most common technologies used to print thermoplastics, thermosetting plastics, and composite materials, such as PLA (a biodegradable thermoplastic polyester derived from natural resources [ 5 , 9 , 10 , 11 ]), PVB (formed from the reaction of an aldehyde and alcohol [ 8 , 12 , 13 ]), and CW (a liquid wax [ 14 , 15 , 16 ]), with complex geometries and a wide range of designs quickly and efficiently [ 5 ]. From the above advantages, 3DP and plastics show great potential for applications in IC, which can help to enable a simple production process and provide design flexibility for complex features.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, to improve the mechanical properties of the printed patterns, acrylonitrile butadiene styrene (ABS) and PC were used as the base and reinforced materials, respectively [ 4 , 5 , 6 , 10 , 17 ]. The tensile properties of PLA structures printed with different infills were investigated [ 9 , 17 , 18 , 19 ]. Moreover, to reduce the roughness surface and shell cracking during burnout, the ABS-printed pattern was coated with a thin layer of wax [ 17 ].…”
Section: Introductionmentioning
confidence: 99%